Halal meats and frozen foods: the halal abattoir, packaging, storage and handling - Amid, Azura (TM-Info-Media Sdn. Bhd., 2009)
In Malaysia we are 'loaded' by many halal meats and halal frozen foods. We take it for granted that we just simply pick any frozen meat or food stamped with the halallogo. Even young children know that if they wanted to buy any packed food, the item must have the familiar Malaysian halal logo.